Current‐Dependent Product Distribution and Reaction Mechanisms of Glycerol Electrooxidation on Nickel - Eva Ng; Camilo A. Mesa; Elena Más‐Marzá; Sixto Giménez (ChemElectroChem)
Abstract The Glycerol Electrooxidation Reaction (GEOR) is a promising alternative to oxygen evolution in electrochemical processes like hydrogen production and CO2 reduction. Although GEOR has attracted increasing attention, its oxidation kinetics in alkaline media are not well understood. In this study, electrochemical characterization and kinetic analysis were conducted using nickel foil as the electrocatalyst. Four galvanostatic conditions (1, 3, 5, and 10 mA cm−2) were evaluated to study product distribution. Increasing the current density from 3 to 5 mA cm−2 led to a fivefold decrease in formate production, indicating a shift in GEOR selectivity within the Oxygen Evolution Reaction (OER) region. At 10 mA cm−2, formate remained as major product, followed by glycolate and glycerate, while tartronate and oxalate production were significantly inhibited, reducing the total Faradaic Efficiency (FE) by half relative to 5 mA cm−2. Rate constants showed increased kinetics for glycerate, glycolate, oxalate, and tartronate as current increased, surpassing formate production at 5 mA cm−2. Spectroelectrochemical measurements revealed the reaction order for GEOR (αGEOR ~1) and OER (αOER ~3), showing that GEOR proceeds via a more efficient oxidative pathway, requiring interaction with just one NiOOH species, while OER involves three highly oxidized Ni‐species.